Case report: Meningioma associated with meningioangiomatosis mimicking invasive meningioma - Ge, Rong; Yang, Jun; Yin, Xiangang; Wang, Jingya (Frontiers in Neurology, 2023)
Meningioangiomatosis (MA) is a rare malformation or hamartomatous lesion in the central nervous system, characterized by a plaque-like mass within the leptomeninges and cerebral cortex. An even rarer condition is MA complicated with meningiomas. We herein report a case of meningioma associated with MA that might be erroneously interpreted as a higher-grade lesion or an invasion by preoperative radiologic and postoperative histological examinations.